Analisis Perencanaan Jarak Celah Udara Pada Generator Axial - Syafriyudin Syafriyudin; M Suyanto (Journal of Electrical Power Control and Automation (JEPCA), 2021)
The generator uses a permanent magnet so it does not require initial excitation to generate a voltage. The generator design is axial flux type, uses ceramic type permanent magnet (NdFeB), uses two flanking stator rotors. For electricity use, the AC voltage is changed to DC voltage using a rectifier for charging the accumulator. The air gap in the axial generator is the distance between the rotor and the stator. The air gap is also a place for the transfer of the magnetic field through the coil on the stator to produce a magnetic flux value that affects the induced voltage in the coil. The faster the rotation, the greater the voltage generated. This axial generator that has been designed can produce a frequency of ± 50 Hz, an effective voltage of ± 22 V when the air gap is 2 mm, the frequency measurement has an error of 10-20 Hz and an error percentage of 5-10%, with the results of measuring the induced current that has a large the same voltage.